2021
DOI: 10.1038/s41375-021-01262-w
|View full text |Cite
|
Sign up to set email alerts
|

Final results of a phase 1b study of isatuximab short-duration fixed-volume infusion combination therapy for relapsed/refractory multiple myeloma

Abstract: Part B of this phase 1b study (ClinicalTrials.gov number, NCT02283775) evaluated safety and efficacy of a fixed-volume infusion of isatuximab, an anti-CD38 monoclonal antibody, in combination with pomalidomide and dexamethasone (Pd) in relapsed/refractory multiple myeloma patients. Isatuximab (10 mg/kg weekly for 4 weeks, then every other week) was administered as a fixed-volume infusion of 250 mL (mL/h infusion rate) with standard doses of Pd on 28-day cycles. Patients (N = 47) had a median of three prior tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Of the 6 participants for whom the response could be evaluated, 3 experienced a minimal response (MR) or better. 53 Another small case series consisting of 9 patients also demonstrated encouraging results for Isa-Pd after daratumumab therapy, with 7 patients showing a MR or better. 54 Mikhael et al reported the effect of single-agent isatuximab in patients who developed daratumumab resistance.…”
Section: Comparison With Daratumumabmentioning
confidence: 90%
“…Of the 6 participants for whom the response could be evaluated, 3 experienced a minimal response (MR) or better. 53 Another small case series consisting of 9 patients also demonstrated encouraging results for Isa-Pd after daratumumab therapy, with 7 patients showing a MR or better. 54 Mikhael et al reported the effect of single-agent isatuximab in patients who developed daratumumab resistance.…”
Section: Comparison With Daratumumabmentioning
confidence: 90%
“…The primary endpoint for Part B was the incidence of Grade (Gr) ≥3 infusion reactions (IRs) during the first six Isatuximab infusions. 64 Forty-seven patients were enrolled. The median duration of exposure was 36.9 weeks.…”
Section: Isatuximabmentioning
confidence: 99%
“…The ORR in all subjects on Part B was 53.2% and 62.2% in Part A, with similar VGPR and CR rates (23.4% and 4.3% in Part B versus 22.2% and 2.2% in Part A, respectively). 64 In another phase Ib study, Isatuximab was combined with Carfilzomib (K) and dexamethasone in 33 RRMM. 65 Patients were previously treated with a median of three lines.…”
Section: Isatuximabmentioning
confidence: 99%
“…To decrease infusion times, numerous trials have confirmed that rapid infusion of daratumumab 90 min and isatuximab 70 min can be initiated safely following evidence of tolerability during the first cycle ( Table 3 ). 23 29 …”
Section: Fda-approved Next-generation Therapeuticsmentioning
confidence: 99%
“…In those patients treated with isatuximab, we utilize a similar prophylactic approach, though montelukast is not included and use of an H2 blocker is continued over the course of treatment. 29 …”
Section: Fda-approved Next-generation Therapeuticsmentioning
confidence: 99%